Autonomy of the Canonical Process and Civil Law Protection of Personal Rights - Rybczyńska-Gryguc, Oliwia (Acta Universitatis Lodziensis. Folia Iuridica, 2024)
The possibility of pursuing claims for the protection of personal rights violated during a trial has been the subject of doctrinal and case law considerations for years. However, in the case of personal rights violated during a trial in an ecclesiastical court, the question arises whether the principle of autonomy of the canonical process does not oppose the protection of personal rights under civil law. In this article, it is argued that the autonomy of the church trial in an ecclesiastical court does not oppose but also does not favour, the civil law way of pursuing one’s rights for the violation of a personal good in an ecclesiastical court. This is primarily due to the limitations of collecting evidence from ecclesiastical trials. The development of legal solutions regulating the issues of cooperation between state and church courts may make it possible to improve the effectiveness of the protection of personal rights violated in canonical trials.